The Bad Guys. 3, The furball strikes back - Blabey, Aaron (New York : Scholastic Press, 2016)
Still yearning to be seen as heroes, Wolf, Shark, Snake, and Piranha set out to rescue ten thousand chickens from a high-tech cage farm--but one unexpected problem is Mr. Snake himself, also known as "The Chicken Swallower."